Analysis of Religious Court Decisions Regarding Heir Rights for Non-Muslims - Yandi, Akmal; Ediz, M. Hidayat; Roszi, Jurna Petri (Sekolah Tinggi Agama Islam Solok Nan Indah, 2023)
Section 171 concerning person who inherits and heir must be a Muslim who has blood relations or marital relations. In case 04/Pdt/2013/ the Bandung Religious Court determined the share of non-Muslim inheritance on the pretext of using a mandatory will. For this reason, research within literature method for case analysis of 04/Pdt/2013/PA Bandung. The results target of this study is determination of Muslim heirs by non-Muslims who are determined by Bandung Religious Court Judge through the determination path number 04/Pdt/2013, if measured through perspective of Islamic Sharia. The judge's determination contradicts the opinion based on the hadith that Muslims do not inherit from infidels and vice versa. Significantly shows the existence of an embargo to become heirs and heirs between people who are Muslims and Non-Muslim. Meanwhile, PA Bandung judges are guided by handful of opinions whose basis is based on general hadith of Prophet and does not discuss inheritance.